HIV/AIDS related perception and behavior: A comparative study among college students of different majors in China - Xinying Sun; Lishi Fan; Chun Chang; Yuhui Shi (Elsevier, 2020)
Objective: In order to carry out proper education and intervention of AIDS based on different features and demands of different majors, this study aimed to compare the difference of college students from six majors in China in the aspects of AIDS-related knowledge, attitudes and behaviors. Methods: A questionnaire survey was carried out among 18,644 students in 30 colleges/universities from 9 provinces of China, who were recruited through stratified cluster sampling. AIDS-related knowledge, attitude, condom-use intention, self-efficacy and sexual behavior of these students were investigated. Results: AIDS-related knowledge level of students majoring in education was the lowest while that of medical students was the highest as well as highest self-efficacy of condom use. Students of music or fine arts had the strongest intention to use condoms, while the students majoring in education had the weakest. The sexually active percentages of male students from different majors ranked as follows: music or fine arts (29.5%), minority nationality (12.2%), science & tech (10.9%), medicine (10.6%), education-major (10.0%), and liberal arts (8.2%). Among female students, the rank was music or fine arts (11.0%), science & tech (6.2%), education-major school (4.5%), minority nationality (4.5%), liberal arts (4.1%), and medicine (2.8%). Conclusion: It is urgent to enhance proper AIDS-related education and intervention based on the features and demands of students from different majors or universities, for example, to enhance comprehensive AIDS prevention education among students major in education and to increase behavioral skills to prevent sexually transmitted diseases among students from colleges or faculty of music or fine arts.